ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO PARA LOS SOCIOS DE LA COOPERATIVA DE TAXIS ONCE DE MAYO DE LA CIUDAD DE LOJA - Orellana Quezada, Sandra Araceli (2019)
The purpose of this study is to improve the socio-economic development of the members of the Taxi Cooperative "Once de Mayo" in the city of Loja, facilitating financing through products and services to promote a culture of saving. The project is composed of four specific studies: Market Study, Technical, Administrative and Legal and Economic-Financial. In order to comply with the proposed objectives, the different methods and techniques applicable to each study were proposed, based on inductive, deductive, analytical methods and techniques such as direct observation, information gathering and survey. In relation to the first objective, the market study was carried out, through the application of surveys to the members of the Taxi Cooperative "Once de Mayo" to find out the degree of acceptance of the Savings Bank and the products and services it would offer. Therefore it was possible to determine which are the people interested in the implementation of the savings bank, the services that will provide which are savings and credit where interest rates will be set according to the benchmarks by the Central Bank of Ecuador always considering the social purpose. Regarding the second objective, a technical study was carried out which consists of the location, size and other elements required for the installation and operation of the Savings Bank, establishing the location of the savings bank, which will be located between Manuel José Aguirre Avenue between Mercadillo and Maximiliano Rodríguez Streets. The Legal Administrative Study indicates the organization of the Savings Bank, for which manuals, statutes and regulations were established that indicate the functions and responsibilities that must be fulfilled by the staff of the entity for an efficient development of activities. The Economic-Administrative Study considered the necessary investment to start up the project, which took into account the fixed and deferred assets and working capital that are indispensable for the execution of the Fund. In addition, the financing will be obtained through the initial contribution, obligatory savings on the part of the partners. As for the financial 5 evaluation, it confirms the viability of the thesis work through its indicators: the Net Present Value, the Internal Rate of Return, the Benefit-Cost Ratio, the Capital Recovery Period and the Sensitivity Analysis. Finally, with all the information obtained in the stages of the work, the respective conclusions and recommendations necessary to carry out the development of the present thesis were presented, in which the acceptance of the members is corroborated and the implementation of the savings bank "ONCE DE MAYO" in the Taxi Cooperative is recommended, thus improving the quality of life of the members, promoting the culture of savings and investment.